The Role of Statins in Prevention of Preeclampsia: A Promise for the Future? - Katsi, Vasiliki; Georgountzos, Georgios; Kallistratos, Manolis S.; Zerdes, Ioannis; Makris, Thomas; Manolis, Athanasios J.; Nihoyannopoulos, Petros; Tousoulis, Dimitris (Frontiers in Pharmacology, 2017)
Preeclampsia has been linked to high morbidity and mortality during pregnancy. However, no efficient pharmacological options for the prevention of this condition are currently available. Preeclampsia is thought to share several pathophysiologic mechanisms with cardiovascular disease, which has led to investigations for the potential role of statins (HMG CoA reductase inhibitors) in its prevention and early management. Pravastatin seems to have a safer pharmacokinetic profile compared to other statins however the existing preclinical evidence for its effectiveness in preeclampsia treatment has been mostly restricted to animal models. This review aims to summarize the current data and delineate the potential future role of statins in the prevention and management of preeclampsia.